2005
DOI: 10.1177/0146167204271309
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious Affective Reactions to Masked Happy Versus Angry Faces Influence Consumption Behavior and Judgments of Value

Abstract: The authors explored three properties of basic, unconsciously triggered affective reactions: They can influence consequential behavior, they work without eliciting conscious feelings, and they interact with motivation. The authors investigated these properties by testing the influence of subliminally presented happy versus angry faces on pouring and consumption of beverage (Study 1), perception of beverage value (Study 2), and reports of conscious feelings (both studies). Consistent with incentive motivation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
441
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(474 citation statements)
references
References 36 publications
25
441
3
5
Order By: Relevance
“…Keep in mind, though, that the treatment comparison between voucher treatments and the Baseline treatment might also be influenced by several effects unrelated to fungibility. For example, it might be that receiving a voucher as gift makes the recipient spend more just because they get into a different mood by receiving a gift (see, e.g., Lewinsohn & Mano 1993, Winkielman et al 2005. Mood changes might also lead to less spending, or spending could be reduced for other reasons, for example because receiving a voucher makes it more salient that the meal has to be paid for at the end.…”
Section: Results Of the Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keep in mind, though, that the treatment comparison between voucher treatments and the Baseline treatment might also be influenced by several effects unrelated to fungibility. For example, it might be that receiving a voucher as gift makes the recipient spend more just because they get into a different mood by receiving a gift (see, e.g., Lewinsohn & Mano 1993, Winkielman et al 2005. Mood changes might also lead to less spending, or spending could be reduced for other reasons, for example because receiving a voucher makes it more salient that the meal has to be paid for at the end.…”
Section: Results Of the Field Experimentsmentioning
confidence: 99%
“…Our results suggest, for instance, that part of the rent increase induced by housing benefits is due to a violation of fungibility. In our view, this problem can be mitigated by 3 For some examples of the extensive research in psychology and marketing on the influence of mood on (consumption) choices, see Kahn & Isen (1993), Lewinsohn & Mano (1993), Groenland & Schoormans (1994, Winkielman et al (2005), or Qiu & Yeung (2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Winkler et al, 2011 found that, although smoking-related cues elicited enhanced positive emotional reactivity using the facial EMG, subjects did not report liking the cues. It is possible that emotional reactions that are too subtle to reach subjective experience still may influence behavior (Childress et al, 2008;Winkielman et al, 2005). It is also possible that the subjective ratings of the drug-related stimuli would increase if there were more conditioning sessions, or higher doses of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…For example, non-conscious pleasure in the form of 'liking' and 'wanting' without subjective awareness of their occurrence has been produced in ordinary people (Winkielman et al 2005). In those people, consumption behavior was altered by subliminal exposure to happy/angry facial expressions, which changed their desire to drink a subsequently encountered beverage and their ratings of its value, even though they felt no conscious emotional reactions at all at the moment their affective reaction was subliminally caused.…”
Section: Pleasure Coding Versus Causalitymentioning
confidence: 99%